Reprezentacja nieznanych spadkobierców przed sądem administracyjnym — wybrane zagadnienia prawa pomocy - Talaga, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The guardian of inheritance may initiate proceedings before an administrative court when the interests of unknown heirs so require e.g. due to the need to determine the tax liability included in the estate. In the case of lodging a complaint to the administrative court by the guardian, he may apply for exemption from court costs because he has not been relieved expressis verbis from incurring them under the law. The guardian of the inheritance may also apply for the appointment of an public attorney because of the right to court, especially when a professional representative is required to draft an appeal. Not always the guardian is a professional attorney advocate, legal counselor, tax advisor who can submit such a remedy by representing the interests of unknown heirs within. In the case of submitting the application with demand of granting the right of assistance it should have been taken into account that the guardian represents the interests of the inheritance. In consequence, the application should present actual information about the inheritance.
Keywords: guardian of inheritance; right of assistance; proceedings before administrative courts; costs of proceedings